Understanding flood seasonality and flood regime shift in the Congo River Basin. Issue 10 (27th July 2022) - Bola, Gode B.; Tshimanga, Raphael M.; Neal, Jeff; Trigg, Mark A.; Hawker, Laurence; Lukanda, Vincent M.; Bates, Paul
ABSTRACT: In the sparsely investigated region of the Congo Basin (CB), flood seasonality and flood regime shift are established through relative frequency, cluster analysis, directional statistics, and non-overlapping block methods based on block maxima and peak over threshold (POT) series. Two months of significantly rich floods are observed at all gauging stations. The spatial distribution of floods presents three patterns: the north and northwest pattern, south and southeast pattern, and west/east pattern. It is observed that unimodal flood distribution is coherent in the northern and southern parts, as opposed to the bimodal flood distribution observed along the large band of the Equator from west to east of the basin. The time lag of flood indices suggests that the flood regime is not stationary. In addition, the time series show periods of high flooding, with POT frequencies and amplitudes higher during the 1960s and early 1970s than any other time period.